WHAT MAKES AN INDIVIDUAL INVEST IN STOCKS? - Candy, Candy (Journal of Global Business and Management Review, 2019)
The purpose of this research is to examine the factors that influence intention to invest in stocks of an individual. This research are using quantitative data with 395 questionnaires collected from Batam residents who as sample. Questionnaire consists indicators for independent variable that included attitude, perceived behavioural control, subjective norms, past behavioral biases and intention to invest. Multiple regression used as the analysis method and result showed that all independent variable have a positive significant effect on intention to invest. It means those factors can motivated an individual to invest in stocks market.